Chemical analysis of some Ocimum basilicum medicinal teas - Daniela Benedec; Diana Rozsa (Rus); Daniela Hanganu; Ilioara Oniga (Amaltea Medical Publishing House, 2021)
Objectives. Ocimum basilicum is one of the widespread medicinal plants, widely used due to its multiple therapeutic properties (antimicrobial, antiviral, hypoglycemic, antispasmodic, anti-inflammatory, carminative, stomachic, antioxidant, analgesic, etc.), as well as its specific aromatic character. The aim of this study was to comparatively investigate the chemical composition (flavonoids, caffeic acid derivatives, tannins, essential oil) of the aerial parts of some Romanian medicinal teas of Ocimum basilicum. Materials and methods. The content of flavonoids, phenolic acids and tannins in three samples of O. basilicum tea were determined spectrophotometrically. Identification of important phenolic compounds (rutin, isoquercitrin chlorogenic acid and caffeic acid) was performed by thin layer chromatography (TLC). The essential oils were obtained by hydrodistillation method. Outcomes and conclusions. Following the quantitative determinations performed, it can be seen that the basil samples are rich in active principles, and their use for the treatment of some diseases can be justified.